Androgen receptor and antiandrogen therapy in male breast cancer. Issue 1 (1st November 2015) - Di Lauro, Luigi; Barba, Maddalena; Pizzuti, Laura; Vici, Patrizia; Sergi, Domenico; Di Benedetto, Anna; Mottolese, Marcella; Speirs, Valerie; Santini, Daniele; De Maria, Ruggero; Maugeri-Saccà, Marcello
Highlights: Male breast cancer is a rare hormone-driven tumor. Molecular studies suggested a role for the androgen receptor. Androgen receptor activation might be fed by aromatase inhibitor administration. Hints of antiandrogen therapy efficacy stemmed from retrospective studies. Abstract: Cancers arising in the male breast are uncommon. Male breast cancer is a hormone-driven disease that often expresses the estrogen receptor, and antiestrogen therapy represents the mainstay of treatment. Paradoxically, the advent of a wave of antiestrogens eclipsed the therapeutic potential of alternative therapeutic options. At the beginning of the hormonal therapy era the administration of antiandrogens to metastatic male breast cancer patients was proposed. Ever since the use of these compounds has largely been neglected. A therapeutic role for antiandrogens has been envisioned again in recent years. First, molecular characterization efforts pointed to the androgen receptor as a potential therapeutic target. Second, the development of aromatase inhibitors unexpectedly raised the need for neutralizing androgens in order to tackle endocrine feedback mechanisms responsible for acquired resistance. We herein provide an overview of molecular studies where the androgen receptor was investigated at the genomic, transcriptomic or phenotypic level. We then discuss androgens in the context of the endocrine networks nourishing male breast cancer. Finally, clinical evidence on antiandrogens is summarized along with strategies should be implemented to improve the medical management of these patients.